Basic mathematics internal use - Ezrinda Mohd Zaihideen; Farahanim Misni; Nadirah Mohd Nasir; Nabilah Alias; Mohd Rashid Ab Hamid; Rahimah Jusoh @ Awang (Penerbit Universiti Malaysia Pahang, 2015)
This course introduces and discusses the fundamental of mathematics focusing on providing a solid theoretical foundation for further work